الضمانات القانونية لتأسيس الأحزاب السياسية في الجزائر - رزيق, عادل (revue mofakir; No 14 (2017): مجلـــة المفكــر, 2018)
It represents one of the most important political parties and institutions in every political systems as an important channel and mechanism of participation in political life mechanisms, which have become a feature of the modern-day attributes. Linked to the above do parties play an important role in raising awareness and the formation of public opinion and guidance, through sponsored by the views and opinions, especially political issues, economic, social, pressing the generality of members of the community and put it on public opinion which is conducive to connecting citizens of their community's issues. The role of political parties on these aspects is not limited to where monitors the work of those in charge of governance so as to prevent perversion and lead to the benefit of the political community as well as its role in influencing the electoral process, providing candidates or helping voters to form convictions which made parties of the most important  corners the democratic system. On this basis, has become the freedom to establish political parties and join them and the exercise of its activities, a human rights and freedoms registered in many international documents and constitutions of most countries And Algeria, along the lines of countries that have been devoted multiparty system in their constitutions since a constitutional amendment in 1989, where he developed a set of legal safeguards that ensurethe right of establishment and activity of political parties.